Study of conformance control in oil sands by oil-in-water emulsion injection using heterogeneous parallel-sandpack models. (15th May 2019) - Ding, Boxin; Yu, Long; Dong, Mingzhe; Gates, Ian
Graphical abstract: Highlights: Heterogeneous parallel-sandpack tests were conducted for conformance control by oil-in-water (O/W) emulsion. Effects of IFT, emulsion quality, droplet size and oil viscosity on conformance control performance are investigated. A carefully designed O/W emulsion can achieve conformance control in severely heterogeneous parallel-sandpack models. A guideline to obtain an optimal emulsion system for conformance control is proposed. Abstract: To improve performance of enhanced recovery processes in heterogeneous oil sands, use of an oil-in-water (O/W) emulsion could be an innovative conformance control technology due to its strong plugging ability. In this study, emulsions were firstly characterized by their distributions of droplet size and interfacial tension (IFT). Parallel-sandpack flow tests were used to investigate the performance of conformance control by O/W emulsion injection. In the first set of parallel-sandpack tests with three different IFT emulsions, it was found that a moderate IFT (0.23 mN/m) emulsion performed well for obtaining a fractional flow ratio of 0.5:0.5. With this moderate IFT, three additional sets of tests were conducted to investigate the impacts of emulsion quality (i.e., oil content), droplet size, and oil viscosity on performance of conformance control. To investigate the conformance control performance in more severely heterogeneous models, more tests were carried out in parallel-sandpack models with permeability ratios of 4:1 and 5:1. Experimental results indicate that a carefully designed O/W emulsion can not only be strong enough to provide sufficient capillary resistance in the high permeability sandpack, but can also be flexible to deform and pass through the pore throats in the low permeability sandpack. Therefore, the droplets can deform and migrate deeply into both the high permeability sandpack and the low permeability sandpack, leading to an ideal fractional flow ratio (0.5:0.5) and achieving a good conformance control in the parallel-sandpack model. A procedure of developing an optimal emulsion system for conformance control has been also proposed for a specific emulsion injection conditions with desired injection rate and emulsion volume.